Protective effect of Dunaliella sp., lipid extract rich in polyunsaturated fatty acids, on hepatic and renal toxicity induced by nickel in rats. (23rd March 2016) - Dahmen-Ben Moussa, Ines; Bellassoued, Khaled; Athmouni, Khaled; Naifar, Manel; Chtourou, Haifa; Ayadi, Habib; Makni-Ayadi, Fatma; Sayadi, Sami; El Feki, Abdelfatteh; Dhouib, Abdelhafidh
Abstract: Aims : The present study was undertaken to investigate the protective effect of lipid extract of Dunaliella sp. (LE) rich in polyunsaturated fatty acids (PUFA), against oxidative stress induced by nickel in experimental rats. Methods : Our investigation evaluated the antioxidant activity of LE using both DPPH and NBT assays. Twenty female albino Wistar rats, randomly allocated into four experimental groups, namely (C): control, (Nit ): nickel-treated rats with 5 mg/kg/d of NiCl2 during 30 days, (LEa ): lipid extract-administered rats with 5  mg/kg BW/d during 30 days and (Nit  +  LEa ): rats treated with Ni and LE-administered during 30 days. Results : The in vitro antioxidant activity demonstrated that LE presents an important antioxidant potential. In vivo, the (Nit  +  LEa ) cotreatment decreased the level of malondialdehyde and restored the antioxidant enzyme activities (superoxide dismutase, catalase and glutathione peroxidase) in livers and kidneys in comparison with those treated with Ni only. LE administration to rats treated with Ni also ameliorated biochemical and histological parameters as compared to only Ni-treated group. LE of Dunaliella sp., rich in polyunsaturated fatty acids showed a significant hepato- and reno-protective effect against metal-induced toxicity. Conclusion : LE of Dunaliella sp., rich in PUFA has been proven to be effective in protection against Ni-induced toxicity.